Determining Critical Points in Fish Distribution and Calculation of Income UD. Sumber Rezeki Laut, Tuban Regency - Iqbal, Muhammad Nur; Mustaruddin, Mustaruddin; Kurniawati, Vita Rumanti; Novita, Yopi (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2024)
This study aims to evaluate the fish distribution activities in UD. Sumber Rezeki Laut, alongside the fish handling during distribution, and critical points of fish quality decline during distribution. This research uses descriptive analysis, critical point analysis, organoleptic tests, and income analysis. Distribution handling is divided into two types, namely direct distribution handling and indirect distribution handling. The most important handling of both types of distribution includes maintaining the right temperature during the process, transferring fish to UD. Sumber Rezeki Laut, changing fish containers, cleaning and soaking fish, and distributing fish to Balekambang Market. However, the long travel distance required to distribute the fishes has the potential to reduce the quality of the fish, as evidenced by the decrease in fish quality observed during the distribution trials. Organoleptic test results showed that the quality of the fish decreased from when it was purchased until it reached the wholesaler. Meanwhile, when calculating distribution costs, the highest result for direct distribution was IDR1,335,987, and the lowest was IDR372,995. The highest income from indirect distribution was IDR1,544,001, while the lowest was IDR399,993. To ensure good fish quality, UD. Sumber Rezeki Laut needs to improve its human resource capabilities to become more efficient and produce quality products for consumers.